GREEN ACCOUNTING AND FINANCIAL PERFORMANCE: EVIDENCE FROM BASIC MATERIALS MANUFACTURING COMPANIES - Eka Chyntia; Siti Maisyarah; Riantari Maharani; Eko Gani PG (Nurul Jadid University, 2025)
This study investigates the impact of environmental costs and environmental performance on financial performance in manufacturing companies within the basic materials sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The research aims to provide empirical evidence on how green accounting practices influence profitability, measured by Return on Assets (ROA). The study employs a quantitative approach with a causal-comparative design, using purposive sampling to select 25 companies that consistently published financial reports and participated in the Ministry of Environment and Forestry’s PROPER program. A total of 75 panel data observations were analyzed. Data were collected through documentation of financial statements, annual reports, and PROPER assessments, and further supported by literature review. Statistical analysis was conducted using descriptive statistics, classical assumption tests, and multiple linear regression with SPSS version 30.0. The results reveal that both environmental costs and environmental performance partially influence financial performance, while simultaneously they significantly affect ROA. These findings indicate that companies in the basic materials sector can achieve a balance between environmental responsibility and financial goals. The study supports legitimacy theory and stakeholder theory, suggesting that proactive environmental strategies not only fulfill regulatory compliance but also enhance firm value. This research contributes theoretically to green accounting in emerging markets and provides practical implications for management in formulating sustainability policies aligned with financial performance.